Labour coefficients reduction and working time reduction - Fadda, Sebastiano (Argomenti, 2016)
The present path and nature of technological innovation is such as to reduce dramatically the labour coefficients in the production processes nearly in every sector and surely in the productive system taken as a whole. This issue, which is linked to the concept of “technological unemployment” evoked by Keynes, is considered both under a theoretical and an empirical perspective, and it leads to explore the most viable way out of the problem of this kind of unemployment, which is the shortening of the working time. The paper explores the complexity, the technical problems and some policy implications of this solution. Finally, some intermediate, less radical, measures in this direction are considered.